2020
DOI: 10.3390/ijms21197151
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of the RNA-Binding Protein SFPQ in Neuronal Function and Neurodegeneration

Abstract: RNA-binding proteins (RBPs) are a class of proteins known for their diverse roles in RNA biogenesis, from regulating transcriptional processes in the nucleus to facilitating translation in the cytoplasm. With higher demand for RNA metabolism in the nervous system, RBP misregulation has been linked to a wide range of neurological and neurodegenerative diseases. One of the emerging RBPs implicated in neuronal function and neurodegeneration is splicing factor proline- and glutamine-rich (SFPQ). SFPQ is a ubiquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 80 publications
0
48
0
Order By: Relevance
“…SFPQ, also known as polypyrimidine tract‐binding protein‐associated splicing factor, PSF, is a predominantly nuclear protein with a range of functions required for cell development and survival, including DNA repair, transcriptional regulation, post‐transcriptional RNA processing, paraspeckle formation and axonal transport [8, 9]. Dysregulation of SFPQ has been linked to multiple neurodegenerative diseases [10]. SFPQ nuclear depletion and altered expression have been reported in animal models and small case–control studies of Alzheimer's disease (AD) and frontotemporal dementia (FTD) [11–13].…”
Section: Introductionmentioning
confidence: 99%
“…SFPQ, also known as polypyrimidine tract‐binding protein‐associated splicing factor, PSF, is a predominantly nuclear protein with a range of functions required for cell development and survival, including DNA repair, transcriptional regulation, post‐transcriptional RNA processing, paraspeckle formation and axonal transport [8, 9]. Dysregulation of SFPQ has been linked to multiple neurodegenerative diseases [10]. SFPQ nuclear depletion and altered expression have been reported in animal models and small case–control studies of Alzheimer's disease (AD) and frontotemporal dementia (FTD) [11–13].…”
Section: Introductionmentioning
confidence: 99%
“…One of such proteins we identified was SFPQ, an ubiquitous and abundant protein implicated in many aspects of nucleic acid biology in the nucleus, ranging from genome stability to transcription, as well as pre-mRNA splicing and 3’end RNA processing or nuclear retention (27). Although SFPQ is strongly localized in the nucleus under normal circumstances, several reports have shown that it may also have important non-nuclear functions such as mRNA post-transcriptional regulation and RNA granule formation especially in neurons (38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it binds to DNA by forming an SFPQ-NONO heterodimer, which participates in homologous DNA pairing and in DNA non-homologous end joining (NHEJ) required for double-strand break repair. Finally, SFPQ is involved in transcriptional regulation as a transcriptional activator [150,151]. Since monotherapies blocking downstream components of the MAPK signaling pathway have been unsatisfactory in CRC because of pathway reactivation, Klotz-Noack and colleagues hypothesized that interference with nuclear proteins activated by MAPK might open a window of opportunity for precisely eliminating MAPK-driven CRCs.…”
Section: Splicing Factor Proline and Glutamine-rich Protein (Sfpq)mentioning
confidence: 99%